2020
DOI: 10.1101/2020.08.10.20172189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Janus Kinase-Inhibitor and Type I Interferon Ability to Produce Favorable Clinical Outcomes in COVID-19 Patients: A Systematic Review and Meta-Analysis

Abstract: Background Novel coronavirus (SARS-CoV-2) has infected over 17 million. Novel therapies are urgently needed. Janus-kinase (JAK) inhibitors and Type I interferons have emerged as potential antiviral candidates for COVID-19 patients for their proven efficacy against diseases with excessive cytokine release and by their ability to promote viral clearance in past coronaviruses, respectively. We conducted a systemic review and meta-analysis to evaluate role of these therapies in COVID-19 patients. Methods MEDLINE … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…A pre-peer-reviewed systematic review of MED-LINE and MedRxiv studies of select immune-based therapies that included type I interferons revealed significantly lower odds of death (OR 0.19, 95% CI 0.04-0.85, P = .03) for recipients of type 1 interferon, but the conclusions are seriously limited by the lack of available randomized controlled studies and inclusion of non-peer-reviewed publications. 18 Collectively these data demonstrate promise for interferon therapy as an adjunct in the treatment of COVID-19 particularly when given early in the course of the infection. However, as has been seen many times thus far in the pandemic, promising results from small preliminary trials of numerous agents have failed when tested in large randomized controlled clinical trials.…”
Section: Covid-19 Curbside Consultsmentioning
confidence: 86%
“…A pre-peer-reviewed systematic review of MED-LINE and MedRxiv studies of select immune-based therapies that included type I interferons revealed significantly lower odds of death (OR 0.19, 95% CI 0.04-0.85, P = .03) for recipients of type 1 interferon, but the conclusions are seriously limited by the lack of available randomized controlled studies and inclusion of non-peer-reviewed publications. 18 Collectively these data demonstrate promise for interferon therapy as an adjunct in the treatment of COVID-19 particularly when given early in the course of the infection. However, as has been seen many times thus far in the pandemic, promising results from small preliminary trials of numerous agents have failed when tested in large randomized controlled clinical trials.…”
Section: Covid-19 Curbside Consultsmentioning
confidence: 86%
“… 45 , 96 Because IFN signaling is instrumental in initiating the innate immune response and in preventing viral replication, JAK-STAT inhibitors should be avoided during the very early stages of the disease. 97 Because preventing the (IFN-triggered) cytokine storm would be highly desirable, attenuating JAK-STAT signaling could very well improve disease outcome when such symptoms are occurring. Indeed, preliminary data from COVID-19 patients treated with the JAK inhibitor baricitinib in the early phases of their disease demonstrated improvements in inflammatory symptoms and in pulmonary function tests.…”
Section: Immunomodulation In Relation To Sars-cov-2mentioning
confidence: 99%
“…An analysis focused on the tractable feedbacks (e.g., target cell depletion and viral load-dependent recruitment of natural killer cells) may obscure the role of the harder to measure and perhaps undefined feedbacks. Importantly, these dynamical processes might all effectively cancel out, such that the most practical approach to probing the immune context to better understand pathology in SARS-CoV-2 and project treatment strategies is simply to identify early cytokine profiles that have been largely shown to dictate disease progression [5] and use these to guide delivery of, e.g., interferons or catch later progression into immunopathology to deliver immunosuppressants [57].…”
Section: Discussionmentioning
confidence: 99%